Status Quo of a CO2-Assisted Steam-Flooding Pilot Test in China. (15th October 2021) - Qi, Zongyao; Liu, Tong; Xi, Changfeng; Zhang, Yunjun; Shen, Dehuang; Mu, Hertaer; Dong, Hong; Zheng, Aiping; Yu, Kequan; Li, Xiuluan; Jiang, Youwei; Wang, Hongzhuang; et al.
Abstract : It is challenging to enhance heavy oil recovery in the late stages of steam flooding. This challenge is due to reduced residual oil saturation, high steam-oil ratio, and lower profitability. A field test of the CO2 -assisted steam flooding technique was carried out in the steam-flooded heavy oil reservoir in the J6 block of the Xinjiang oil field (China). In the field test, a positive response to the CO2 -assisted steam flooding treatment was observed, including a gradually increasing heavy oil production, an increase in the formation pressure, and a decrease in the water cut. The production wells in the test area mainly exhibited four types of production dynamics, and some of the production wells exhibited production dynamics that were completely different from those during steam flooding. After being flooded via CO2 -assisted steam flooding, these wells exhibited a gravity drainage pattern without steam channeling issues, and hence, they yielded stable oil production. In addition, emulsified oil and CO2 foam were produced from the production well, which agreed well with the results of laboratory-scale tests. The reservoir-simulation-based prediction for the test reservoir shows that the CO2 -assisted steam flooding technique can reduce the steam-oil ratio from 12 m 3 (CWE)/t to 6 m 3 (CWE)/t and can yield a final recovery factor of 70%.